2010
DOI: 10.4176/091024
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness Among Depressed Patients

Abstract: BackgroundExcessive daytime sleepiness (EDS) has been reported among depressed patients in many populations. Many depressed patients seek medical attention partly to deal with EDS, but this sleep disorder is often overlooked in clinical practice.ObjectivesThe objectives of this study were to determine the prevalence of EDS among depressed patients and determine its relationship with the severity of depression.MethodsSixty-seven patients diagnosed with depressive episode took part in the study. The severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 16 publications
1
12
1
Order By: Relevance
“…This was comparable to the work of Chellappa and colleagues [26] who reported 42.8% and to the (44.8%) reported by Mume et al [27] but lower than 57.2% reported by Chellappa [26]. This result was higher than that obtained from analysis of the Geolong Osteoporosis Study, where 13% of the 844 women surveyed were found to have EDS, as measured by the Epworth Sleepiness Scale.…”
Section: Discussioncontrasting
confidence: 55%
“…This was comparable to the work of Chellappa and colleagues [26] who reported 42.8% and to the (44.8%) reported by Mume et al [27] but lower than 57.2% reported by Chellappa [26]. This result was higher than that obtained from analysis of the Geolong Osteoporosis Study, where 13% of the 844 women surveyed were found to have EDS, as measured by the Epworth Sleepiness Scale.…”
Section: Discussioncontrasting
confidence: 55%
“…Lack of facilities for conducting sleep studies and management of sleep disorders were limitations in the study. The weakness in the health system's ability to provide readily accessible and available services for sleep disorders, as observed in this study and other studies from the country, 7,8 is probably influenced by the health systems need to address other more common childhood disorders. Improving the health system's capacity to manage sleep disorder would enhance awareness, promote favorable outcomes and strengthen health care delivery in general.…”
Section: Discussionmentioning
confidence: 66%
“…Psycho social implications of hypersomnia have been reported from other regions of the world as well as the dearth of facilities for sleep studies in the country. [1][2][3]7,8 It took seven years and a significant progressive deterioration in academic in performance before a concerted effort was undertaken by his caregivers to unravel the disorder. It underscores the poor degree of awareness about sleep disorders in the patient's immediate environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations